Anticoagulation in patients with impaired renal function and with haemodialysis: anticoagulant effects, efficacy, safety, therapeutic options = Antikoagulation bei Patienten mit eingeschränkter Nierenfunktion und Hämodialyse - Harenberg, Job; Krämer, Roland; Weiß, Christel; Krämer, Bernhard; Wehling, Martin (Hämostaseologie, 2015)
Patients with impaired renal function are exposed to an increased risk for bleeding complications depending on the amount of the anticoagulant eliminated by the kidneys. The elimination of unfractionated heparins, vitamin K antagonists and argatroban is only minimally influenced by a reduced renal function. Low-molecular weight heparins, fondaparinux, danaparoid, hirudins and non-vitamin K antagonist oral anticoagulants (NOAC) cause a variably increased bleeding risk in renal impairment. Dose reductions are recommended for all of these anticoagulants in renal impairment, some are even contraindicated at certain levels of renal impairment. Their benefit over the conventional anticoagulants is preserved if renal dosing is employed. For end-stage renal disease patients specific treatment regimens are required.